Atypical Aeromonas salmonicida -infection as a threat to farming of Arctic charr (Salvelinus alpinus L.) and European grayling (Thymallus thymallus L.) and putative means to prevent the infection - Pylkkö, Päivi (University of Jyväskylä, 2004)
Tiivistelmä ja 5 erip. Verkkojulkaisussa ei ole eripainoksia. v 2004 ok Diss. : Jyväskylän yliopisto, 2004